Novel method for the protection of amino alcohols and carbonyl compounds over a heterogeneous, reusable catalyst - Srivastava, P.; Srivastava, R. (Catalysis Communications, 2008)
A novel application of Al-SBA-15 catalyst in the protection of amino alcohols and carbonyl compounds is reported. N-t-butoxy carbonyl [N(Boc)] amino alcohols were protected using 2,2-dimethoxyproparic (DMP) to form acetonides. Acetonide deprotection was also studied using the same catalyst to obtain the parent amino alcohol. Protection of carbonyl compounds was Studied using neopentyl glycol, ethylene glycol and propylene glycol as the protecting agents. A series of commercially important molecules Such as 2-substituted and 2,2-disubstituted 1,3-benzodioxoles were synthesized by reacting carbonyl compounds with catechol. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Acetalization; acetonide; Amino alcohol; benzodioxole; protection

Facile enantioselective synthesis of (S)-N-(5-chlorothiophene-2-sulfonyl)-beta,beta-diethylalaninol via proline-catalyzed asymmetric alpha-aminooxylation and alpha-amination of aldehyde - Rawat, Varun; Chouthaiwale, Pandurang V.; Chavan, Vilas B.; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2010)
A high-yielding enantioselective synthesis of the bioactive (S)-N-(5-chlorothiophene-2-sulfonyl)beta,beta-diethylalaninol (1), a Notch-1-sparing gamma-secretase inhibitor metabolite (with EC50 = 28 nM) effective in reduction of All production in vivo, has been realized starting from readily available 3-pentanone. The key steps of the synthesis are proline-catalyzed alpha-aminooxylation and alpha-amination of aldehyde: the latter contributing an overall yield of 45.2% and 98% ee. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amination; alpha-Aminooxylation; Alzheimer's disease; Amino alcohol; Proline

Stereoselective synthesis of (-)-galantinic acid - Dubey, Abhishek; Harbindu, Anand; Kumar, Pradeep (Synthesis-Stuttgart, 2011)
An efficient and highly concise synthesis of (-)-galantinic acid has been achieved using an asymmetric allylation reaction of Garner's aldehyde.
Keywords: Amino alcohol; Chiral pool; iterative asymmetric allylation; Oxidation; stereoselective synthesis

Synthesis and antitubercular activity of amino alcohol fused spirochromone conjugates - Mujahid, Mohammad; Gonnade, Rajesh G.; Yogeeswari, P.; Sriram, D.; Muthukrishnan, Murugan (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 21 new amino alcohol fused spirochromone conjugates have been synthesized, characterized with analytical data and evaluated their antimycobacterial activity against Mycobacterium tuberculosis (virulent strain H37Rv) in vitro. Some of the compounds exerted significant inhibition, in particular, compound 4f found to be the most potent derivative exhibiting MIC = 3.13 mu g/mL. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Amino alcohol; Antitubercular activity; Mycobacterium tuberculosis; Spirochromones